Analisis Perkembangan Sosial-Emosional di Sekolah Dasar - Yulinda Sari; Nur Amelia Sari; Rahmi Adiffa S.A; Sri Suwartini (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to identify: (1) how students' social-emotional development occurs during the learning process, (2) social-emotional development outside the learning context, and (3) teacher strategies in supporting this development. The results of the study indicate that in the classroom, students show positive attitudes such as actively participating, communicating and interacting, being able to adapt in groups, and being confident. Outside the classroom, students are seen to be able to help friends, not force their desires, being able to resolve conflicts while playing, and being able to control their emotions. Teachers' efforts in supporting social-emotional development include building positive relationships, being role models, and providing consistent guidance and direction.